Atomic Scale Studies of La/Sr Ordering in Colossal Magnetoresistant La2−2xSr1+2xMn2O7 Single Crystals. (29th September 2014) - Roldan, Manuel A.; Oxley, Mark P.; Li, Qing'an; Zheng, Hong; Gray, K. E.; Mitchell, J. F.; Pennycook, Stephen J.; Varela, María
Abstract To date, it is unclear whether chemical order (or disorder) is in any way connected to double exchange, electronic phase separation, or charge ordering (CO) in manganites. In this work, we carry out an atomic resolution study of the colossal magnetoresistant manganite La2−2xSr1+2xMn2O7 (LSMO). We combine aberration-corrected electron microscopy and spectroscopy with spectroscopic image simulations, to analyze cation ordering at the atomic scale in real space in a number of LSMO single crystals. We compare three different compositions within the phase diagram: a ferromagnetic metallic material (x=0.36), an insulating, antiferromagnetic charge ordered (AF-CO) compound (x=0.5), which also exhibits orbital ordering, and an additional AF sample (x=0.56). Detailed image simulations are essential to accurately quantify the degree of chemical ordering of these samples. We find a significant degree of long-range chemical ordering in all cases, which increases in the AF-CO range. However, the degree of ordering is never complete nor can it explain the strongly correlated underlying ordering phenomena. Our results show that chemical ordering over distinct crystallographic sites is not needed for electronic ordering phenomena to appear in manganites, and cannot by itself explain the complex electronic behavior of LSMO.